(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
. Adolescence is one of the most complex stages in the psychological, emotional and social development of a person. During this period, the formation of aggressive behavior is strongly influenced by various factors - family environment, relationships with peers, psychological state at school and the content of the media. In particular, conflicts between parents, lack of control or excessive severity can increase internal conflicts in a teenager and lead to the emergence of an aggressive reaction. Peer pressure and difficulties in social adaptation also contribute to the formation of aggression. In addition, violent games, films and Internet content can have a negative impact on the behavior of adolescents, encouraging them to repeat aggressive patterns. Research shows that psychological support, healthy communication and positive parenting strategies play an important role in preventing aggression.